PENGELOLAAN KAWASAN EKOWISATA HUTAN MANGROVE - Eka; Trio Saputra; Wasiah Sufi (PT. Jurnal Center Indonesia Publisher, 2024)
Mangrove forest management is important in efforts to preserve the environment in coastal areas. This activity is a good step to reduce damage to the mangrove ecosystem and maintain coastal damage. The research aims to find out the condition and development of the management of the Mangrove Forest Ecotourism Area. Based on the research results, there are several things that are still not running well, which can be seen from the lack of planning, organizing documents, lack of coordination and supervision of ecotourism management which is still less organized and structured, which can be seen from the absence of a fixed or routine schedule for monitoring ecotourism. Pangkalan Sesai mangrove forests, infrastructure, bridges that are no longer passable by visitors. Knowledge about tourism is still lacking and maintenance carried out by managers is not optimal. Then the addition of other attractions and road improvements to make visitors more comfortable, where accessibility is an important factor in the visiting sector